2023
DOI: 10.1021/acsptsci.2c00253
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Aryl Hydrocarbon Receptor-Mediated Cancer Cell-Selective Apoptosis in Triple-Negative Breast Cancer Cells by a High-Affinity Benzimidazoisoquinoline

Daniel J. Elson,
Bach D. Nguyen,
Sebastian Bernales
et al.

Abstract: Triple-negative breast cancer (TNBC) remains a disease with a paucity of targeted treatment opportunities. The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that is involved in a wide range of physiological processes, including the sensing of xenobiotics, immune function, development, and differentiation. Different small-molecule AhR ligands drive strikingly varied cellular and organismal responses. In certain cancers, AhR activation by select small molecules induces cell cycle arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Collectively, analogues that contained substituents on the phenyl ring (4 and 6-9) including our lead (3) or alterations to the imidazole (13) ring presented with low to moderate growth inhibition (Table 1), suggesting that phenyl ring substituents hinder their biological action. This was further exemplified by analogue 5, the simplest BBQ compound that lacked a phenyl ring substituent, but which induced strong growth inhibition (GI 50 0.001 μM) and 3200-fold selectivity in MDA-MB-468 cells compared with normal breast cells, also previously reported (Elson et al, 2023). In contrast, analogues containing moieties in the naphthyl rings maintained (10) or enhanced growth inhibition potency (11).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Collectively, analogues that contained substituents on the phenyl ring (4 and 6-9) including our lead (3) or alterations to the imidazole (13) ring presented with low to moderate growth inhibition (Table 1), suggesting that phenyl ring substituents hinder their biological action. This was further exemplified by analogue 5, the simplest BBQ compound that lacked a phenyl ring substituent, but which induced strong growth inhibition (GI 50 0.001 μM) and 3200-fold selectivity in MDA-MB-468 cells compared with normal breast cells, also previously reported (Elson et al, 2023). In contrast, analogues containing moieties in the naphthyl rings maintained (10) or enhanced growth inhibition potency (11).…”
Section: Discussionmentioning
confidence: 72%
“…Our efforts have generated the halogenated aryl hydrocarbon ANI-7 (1; (Z)-2-(3,4-dichlorophenyl)-3-(1H-pyrrol-2-yl)acrylonitrile) and the polyaromatic hydrocarbon NAP-6 (2; (Z)-2-(2-aminophenyl)-1H-benzo[de]isoquinoline-1,3(2H)-dione) (Figure 1) as two molecules displaying more than 500-fold selective targeting of certain breast cancer cell lines compared with normal breast cells or other tumour types via activation of the AhR pathway (Gilbert et al, 2017;Gilbert et al, 2020). We have also demonstrated that 10-Cl-BBQ (3; 10-chloro-7H-benzo[de]benzo [4,5]imidazo[2,1a]isoquinolin-7-one) (Figure 1), a known AhR ligand, is up to 150fold selective in targeting certain breast cancer cell lines compared with normal cells or other tumour types (Baker et al, 2021a;Elson et al, 2023). Leveraging this data, we sought to further explore the breast cancer selectivity and activation of the AhR/CYP1/ SULT1A1 axis of a library of substituted BBQ analogues, in cell line models of the disease.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Viability assays , were performed using CellTiter-Glo assay (Promega, CA, Cat #G7573) as per the manufacturer’s instructions. DAPI stain was used to assess apoptosis. Colony-forming assays were performed as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, constitutive AhR activity has been reported in multiple BC models of humans and rodents, complemented by recurring inflammatory elements. Hence AhR overexpression in TNBC cells presents a tractable therapeutic paradigm . Genome-wide association studies combined with large-scale data obtained through multigene paneling have revealed PALB2, TP53, PTEN, STK11, BRCA1, and BRCA2 as the TNBC high-penetrance (HP) genes.…”
Section: Introductionmentioning
confidence: 99%